Pelatihan Pelayanan Prima untuk Meningkatkan Kepuasan Konsumen Pelayanan Satu Pintu - Asti Widayanti; Irna Yuniar; Kastaman Kastaman; Raswyshnoe Boing Kotjoprayudi; Idola Perdini Putri; reni nuraeni (To Maega : Jurnal Pengabdian Masyarakat, 2023)
Public Service Mall (MPP) is a place for providing public services, both goods and services, at one door, one place, the purpose of MPP is to provide fast, easy, and accountable services. MPP in Kabupaten Bandung under the coordination of The Investment and One-Stop Integrated Services (DPMPTSP) involves services from 17 public institution in Kabupaten Bandung. Variations in types of services and variations in consumers require service personnel to always provide excellent service. The purpose of Community Service is to provide training on the basic stages of service excellent as part of increasing customer satisfaction. The method used in this activity is through interviews to determine training needs, excellent service training using two approachs are service attitude and service communication. This activity was attended by 31 participants consisting of front office staff from civil servants, non-PNS and security personnel. The output of this activity was in the form of a training material module. The evaluation results showed that 99,35% of the participants were satisfied with the implementation of the training and hoped that the training could be carried out consistently